Manajemen Kurikulum di Lembaga PAUD (Tinjauan Terhadap Implementasi dan Tantangannya) - Minarsih (Jurnal Studi Pendidikan Anak Usia Dini, 2025)
This research discusses curriculum management in Early Childhood Education (ECED) institutions. ECD plays a crucial role in children's early development before entering formal education. However, curriculum management in PAUD is often faced with unique challenges such as developing a developmentally appropriate curriculum, effective implementation, and managing limited resources. This study uses qualitative research methods by collecting data through in-depth interviews with PAUD managers, direct observation, and analysis of related documents. The findings show that curriculum management in PAUD requires a holistic and sustainable approach. Key factors that emerged included curriculum development based on local needs and child characteristics, active involvement of parents in the education process, and training and professional development for educators. The results of this study provide insight into effective strategies for managing curriculum in ECD institutions, emphasizing the importance of adaptability, collaboration and the application of teaching techniques that are in line with the principles of early childhood education. The implications of this research can support the development of better education policies and improve the quality of early education for children in Indonesia